Electrical properties of YSZ/NiO composites prepared by a liquid mixture technique - Esposito, V; de Florio, D. Z.; Fonseca, F. C.; Muccillo, ENS; Muccillo, R.; Traversa, E. (Elsevier B.V., 2005)
We report the preparation and characterization of yttria-stabilized zirconia/nickel oxide composites (YSZ/NiO). This composite is the precursor material of the cermet YSZ/Ni, which is used as solid oxide fuel cell anode material. The performance of the anode is strongly dependent on the microstructural properties of the cermet. Therefore, the control of the microstructure of the YSZ/NiO composite is a key step for the fabrication of high-performance anodes. In this study, the composites were prepared by a modified liquid mixture technique. Scanning electron microscopy analysis evidenced the good dispersion of the phases and that NiO nanoparticles are spread over the YSZ surface. Sintered pellets were studied by X-ray diffraction and impedance spectroscopy. The main results show that the composite is comprised of a well-dispersed mixture of the two phases. The electrical conductivity data show that there is a strong dependence of the transport mechanism on the relative composition of phases. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: mixed conductor; composite; electrical properties; solid oxide fuel cells (SOFC)